2023
DOI: 10.1002/adma.202302275
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Narrow‐Bandwidth Deep‐Red Electroluminescence Based on Green Plant‐Derived Carbon Dots

Abstract: Deep‐red light‐emitting diodes (DR‐LEDs, >660 nm) with high color‐purity and narrow‐bandwidth emission are promising for full‐color displays and solid‐state lighting applications. Currently, the DR‐LEDs are mainly based on conventional emitters such as organic materials and heavy‐metal based quantum dots (QDs) and perovskites. However, the organic materials always suffer from the complicated synthesis, inferior color purity with full‐width at half‐maximum (FWHM) more than 40 nm, and the QDs and perovskites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Xylan with good RTP performance is chosen to prepare CPDs because it is a paper-mill or viscose fiber-mill byproduct that is normally cast aside, which is highly low-cost and eco-friendly. More importantly, unlike other biomass (such as cucumber skin, fruits, rice husks, and green plant) used to synthesize CDs, xylan composed of β-(1 → 4)-linked backbones of xylose possesses a well-defined structure, conductive to theoretically elucidate the relationship between structure and PL performance (will discuss below). Carboxyl groups are grafted on xylan chains by carboxymethylation to afford water-soluble carboxymethyl xylan (CMX) (Figures S2 and S3).…”
Section: Resultsmentioning
confidence: 99%
“…Xylan with good RTP performance is chosen to prepare CPDs because it is a paper-mill or viscose fiber-mill byproduct that is normally cast aside, which is highly low-cost and eco-friendly. More importantly, unlike other biomass (such as cucumber skin, fruits, rice husks, and green plant) used to synthesize CDs, xylan composed of β-(1 → 4)-linked backbones of xylose possesses a well-defined structure, conductive to theoretically elucidate the relationship between structure and PL performance (will discuss below). Carboxyl groups are grafted on xylan chains by carboxymethylation to afford water-soluble carboxymethyl xylan (CMX) (Figures S2 and S3).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the voids in ZnMgO films can be effectively filled with PVP molecules to form dense films to efficiently reduce the leakage current. 59 Therefore, for the fabricated devices, insulating polymer PVP was introduced into the ETL based on ZnMgO nanoparticles to modulate the electron mobility. The EL spectra of CDs-LEDs with different ratios of ZnMgO and PVP are compared in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S15 (ESI†) that no new light energy groups appear, that is, no chemical reaction occurs to produce new substances, thus the EL spectrum of the device is a composite spectrum. 58,59 When the doping ratio of CBP&CDs is 1 : 8, the fabricated CDs-LED with CIE coordinates of (0.30, 0.47) is obtained (Fig. 4(b)), corresponding to green light emission.…”
Section: Resultsmentioning
confidence: 99%
“…47,48 However, it is notable that this issue was recently successfully addressed by Chen and co-workers when they synthesized clover-derived bio-CDs, which delivered emission with a narrow FWHM of 25 nm in an OLED device. 49…”
Section: Introductionmentioning
confidence: 99%